Trust and In-Group Favoritism in a Culture of Crime - Stephan Meier; Lamar Pierce; Antonino Vaccaro (Institute for the Study of Labor (IZA), 2014)
We use experiments in high schools in two neighborhoods in the metropolitan area of Palermo, Italy to experimentally demonstrate that the historical informal institution of organized crime can undermine current institutions, even in religiously and ethnically homogeneous populations. Using trust and prisoner's dilemma games, we found that students in a neighborhood with high Mafia involvement exhibit lower generalized trust and trustworthiness, but higher in-group favoritism, with punishment norms failing to resolve these deficits. Our study suggests that a culture of organized crime can affect adolescent norms and attitudes that might support a vicious cycle of in-group favoritism and crime that in turn hinders economic development.
Keywords: C91; C92; 330; organized crime; trust; in-group favoritism; Mafia